Effect of Moringa Leaves Oral Supplementation on Pro-Inflammatory Cytokines in PEM Conditions - Aquarista, Nita; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih (Indonesian Journal of Global Health Research, 2024)
Protein-Energy Malnutrition (PEM) is a nutritional problem resulting from protein or energy deficiency, often associated with the occurrence of infections. Infections due to weakened immune systems caused by protein deficiency can lead to inflammation. The flavonoid content in moringa oleifera leaf (MOL) has anti-inflammatory that can be utilized as an alternative treatment for PEM. Objective: To identified the potential of MOL as an anti-inflammatory in PEM conditions. Method: This study is a systematic literature review that were obtained through Google Scholar, ScienceDirect and PubMed databases for the last 10 years from 2012 to 2022 with a total 80 articles found based on keyword searches. References then re-selected using PICOS method, resulting in 9 articles be reviewed. The review process involves gathering pertinent information that is applicable to the study objectives and analyzing it based on population/problems, intervention or management to the case, comparating the similarities and differences, study the outcome and study design of the previous articles. Then the information will be synthesized to conclude the review. Results: The findings indicate that MOL can be used effectively for patient with PEM as an anti-inflammatory agent by reducing the secretion of pro-inflammatory cytokines such as IL-1, IL-6 and TNF-α Conclusions: Administration of oral supplementation of MOL has a positive impact as an anti-inflamatory in PEM condition.